Fray Ángel Maldonado: el fallido cambio de obispado, 1712-1714 - Selene del Carmen García Jiménez (Nuevo mundo - Mundos Nuevos, 2018)
The change of bishops was a common event in New Spain where it was the prerogative of the fount of honour (Patronato Regio). However, the case of bishop friar Ángel Maldonado is special because he opposed the king's mandate for him to abandon the diocese of Antequera (Oaxaca) and occupy the one in Orihuela (Spain). Maldonado retained his position in Oaxaca until his death, despite all the opposing factors. The following lines present this case study, explaining the causes behind Maldonado’s reassignment and the resources used by the bishop to maintain the episcopal polity.